Vagus nerve bundle stimulation using 1505‐nm laser irradiation in an in‐vivo rat model. Issue 1 (26th September 2021) - Yetis, Ozan; Guner, Ozge; Akkaya, Ibrahim; Guneli, Ensari; Bagriyanik, Alper; Tozburun, Serhat
Abstract: Laser nerve stimulation using near‐infrared laser irradiation has recently been studied in the peripheral nervous system as an alternative method to conventional electrical nerve stimulation. Bringing this method to the vagus nerve model could leverage this emerging stimulation approach to be tested in broader preclinical applications. Here, we report the capability of the laser nerve stimulation method on the rat vagus nerve bundle with a 1505‐nm diode laser operated in continuous‐wave mode. Studies of the stimulation threshold and laser‐induced acute thermal injury to the nerve bundle were also performed to determine a temperature window for safe, reliable and reproducible laser stimulation of the rat vagus nerve bundle. The results show that laser stimulation of the vagus nerve bundle provides reliable and reproducible nerve stimulation in a rat model. These results also confirm a threshold temperature of >42°C with acute nerve damage observed above 46°C. A strong correlation was obtained between the laser time required to raise the nerve temperature above the stimulation threshold and the mean arterial pressure response. Advantages of the method such as non‐contact delivery of external stimulus signals at mm scaled distance in air, enhanced spatial selectivity and electrical artefact‐free measurements may indicate its potential to counteract the side effects of conventional electrical vagus nerve stimulation . Abstract : Laser nerve stimulation has recently been studied in the peripheral nervous system as an alternative method to conventional electrical nerve stimulation. The results presented in this study may be useful to bring the advantages of the method, such as non‐contact delivery of external stimulus signals at mm scaled distance in air, relatively and superficially enhanced spatial selectivity and electrical artefact‐free measurements to vagus nerve stimulation studies.